Influence of different BFO filler content on microwave absorption performances in BiFeO3/epoxy resin composites - Rusly S.N.A.; Ismail I.; Matori K.A.; Abbas Z.; Shaari A.H.; Awang Z.; Ibrahim I.R.; Idris F.M.; Mohd Zaid M.H.; Mahmood M.K.A.; Hasan I.H. (Elsevier Ltd, 2024)
Indexed by WOS/Scopus/ERA